(untitled) - Grant, John (New York, 1993)
From Mickey Mouse to Timon, Roger Rabbit to Hades, and Aladdin to Sebastian--the famous, the infamous, and the obscure--every character of the Disney honor roll is present and accounted for in this comprehensive volume that every true Disney fan and animation enthusiast will treasure.
Keywords: Walt Disney company,Cartoon characters,Disney characters,Công ty Walt Disney,Nhân vật hoạt hình,Nhân vật Disney; United States